2023
DOI: 10.2147/ndt.s421092
|View full text |Cite
|
Sign up to set email alerts
|

The Correlation Between Night Shift Work Schedules, Sleep Quality, and Depression Symptoms

Abstract: Purpose Poor sleep and depressive symptoms are two negative effects of night shift work on physical and mental health. This study evaluated the correlation between sleep quality and depression symptoms among nurses in Saudi Arabia. Specifically, we assessed depressive symptoms and sleep quality observed among nurses who worked night shifts and compared the outcomes with those who worked exclusively day shifts in hospital settings. Patients and Methods A total of 191 par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 45 publications
0
3
0
1
Order By: Relevance
“…Alreshidi et al . [ 16 ] postulated a close relationship among circadian rhythm disruption, sleep quality and depressive symptoms, on the grounds that night shifts may disrupt nurses’ circadian rhythms and negatively affect sleep, subsequently inducing depressive symptoms. The current study offers an analysis from this point of view and identifies daily sleep duration as one of the factors influencing the occurrence of depression in psychiatric nurses, citing nurses with a sleep duration of 7 h being at a relatively higher risk of depression compared to nurses with a daily sleep duration of 7 h per day.…”
Section: Discussionmentioning
confidence: 99%
“…Alreshidi et al . [ 16 ] postulated a close relationship among circadian rhythm disruption, sleep quality and depressive symptoms, on the grounds that night shifts may disrupt nurses’ circadian rhythms and negatively affect sleep, subsequently inducing depressive symptoms. The current study offers an analysis from this point of view and identifies daily sleep duration as one of the factors influencing the occurrence of depression in psychiatric nurses, citing nurses with a sleep duration of 7 h being at a relatively higher risk of depression compared to nurses with a daily sleep duration of 7 h per day.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the types of occupation were a significant predictor of the level of depression. The results of previous studies found that doing night shift work in health professions was not associated with depression, but doing night shift work outside of health professions may increase the risk of depression (Angerer et al, 2017); (Lee et al, 2017) (Alreshidi & Rayani, 2023).…”
Section: Occupation Living Circumstances and Depressionmentioning
confidence: 91%
“…4 Wolkow ve arkadaşlarının itfaiye görevlilerini değerlendirdiği çalışmada ise çalışanların GVS'de çalışması ve uzun vardiyalarda kısa süreli dinlenmesinin mesleki tükenmişlik ile ilişkili olduğu görülmüştür. 19 21 Lim ve arkadaşları fabrika işçilerini değerlendirdikleri bir çalışmada GVS'de çalışan bireylerin uyku kalitesinin gündüz çalışan personele göre daha kötü olduğunu belirtmiştir. 22 Benzer şekilde bizim çalışmamızda da gönüllüler GVS'de çalışmaya başladıktan sonra uyku kaliteleri belirgin şekilde bozulmuştur.…”
Section: Gvs öNcesi Uyku Kalitesiunclassified